The flexural properties of oil palm trunk (OPT) impregnated with epoxy (OPTE) composite manufactured by vacuum-assisted resin transfer moulding (VARTM) technique. (May 2023) - Nik Wan, F.; AbuBakar, A.; Suriani, M.J.; Saat, A.M.; Fitriadhy, A.; Wan Nik, W.B.; Abdul Majid, M.S.; Mukhtar, Z.Z.
Highlights: The OPTE composites were fabricated from VARTM technique. Three different zones of OPTE composite were assigned. Epoxy impregnated in OPT improved the flexural properties of OPTE composite. The correlation between flexural strength and MOE were predicted by using linear regression study. Abstract: Nowadays, the utilization of oil palm trunk (OPT) biomass has gained more interest in composite applications. This research presents the flexural properties of unimpregnated OPT and OPT impregnated with epoxy (OPTE) composites. The OPTE composites were fabricated using the vacuum-assisted resin transfer moulding (VARTM) technique. The unimpregnated OPT and OPTE composite specimens were selected from three different zones of longitudinal zone OPT namely Zone I (outer), Zone II (middle) and Zone III (inner), respectively. The flexural test was conducted according to ASTM D790. The results showed promising increases in flexural strength and flexural modulus of the OPTE composite in Zones I, II, and III compared to unimpregnated specimens, with increases of 254.09 % (49.79 MPa) and 158.78 % (4.14 GPa) in Zone I, 297.43 % (37.28 MPa) and 309.51 % (3.58 GPa) in Zone II, and 242.67 % (29.34 MPa) and 305.84 % (2.94 GPa) in Zone III, respectively. There was positive trend linear regression significantly observed in the relationship between flexural strength and modulus of elasticity (MOE) of OPTE composites and unimpregnated OPT of all three zones, respectively. The fractured flexural specimens of three different zones were analysed by using scanning electron microscopy (SEM). The improvement of OPTE composites is a possible as an alternative to replace the existence of commercial wood.